Sammy Keyes and the hotel thief / Wendelin Van Draanen - Draanen, Wendelin Van
Thirteen-year-old Sammy's penchant for speaking her mind gets her in trouble when she involves herself in the investigation of a robbery at the "seedy" hotel across the street from the seniors' building where she is living with her grandmother.